Anti-terrorism, citizenship and security - Jarvis, Lee; Lister, Michael (Book collections on Project MUSE., 2015)
Since 9/11, the UK's anti-terrorism framework has undergone dramatic changes. Drawing on primary empirical research, this study examines the impact of these on security and citizenship, as perceived by citizens themselves. Engaging with different communities across the UK, it argues that although white individuals are not unconcerned about the effects of anti-terrorism powers, ethnic minority citizens believe that anti-terrorism measures have had a direct and negative impact on various dimensions of their citizenship and security.